Sistem Pakar dalam Menganalisis Penyakit Organ dan Jaringan Tubuh dengan Metode Perceptron dan Fitur Augmented Reality - Eryanto Agusriadi; Finot (Jurnal Informasi dan Teknologi, 2022)
Diseases of organs and tissues of the body or in medicine are commonly referred to as anatomical pathology. Is a medical specialist who deals with the diagnosis of disease based on gross, microscopic and molecular examination of organs, tissues and cells. This procedure is used to identify abnormalities in the body and can help diagnose disease. This study aims that the results of the analysis of the perceptron method can help the doctors of the Putri Hijau Hospital in Medan City quickly and precisely in identifying and analyzing patients with anatomical pathologies. The data processed in this study were 50 patients from the hospital, sourced from one of the anatomical pathology specialists at the hospital. Then the results of the data that have been obtained from patients with the perceptron method using an android-based application. So that the results of the diagnosis of the patient's disease can be obtained. The results of research with this method produce a system that can assist anatomical pathology specialists to present disease diagnosis information at the Putri Hijau Hospital in Medan City. With the existence of an expert system in analyzing diseases of organs and body tissues, it can be recommended to help specialists in anatomical pathology to diagnose patients more quickly and precisely.